A microbiological study of the rhizosphere of Pterocarpus indicus - Quebec, Winston Felix J. (1984)
This research deals with the microbiological study of the rhizosphere of the Pterocarpus indicus. The rhizosphere and non-rhizosphere and their difference tested through the statistical tool called the t-test. The presence of Rhizobium sp. in the root nodules is determined. The results obtained indicates that the microbial population of the rhizosphere and non-rhizosphere soil areas of the Pterocarpus indicus are quantitatively and significantly different. The presence of Rhizobium sp. in the root nodules was established.